Properties of Exponentiation

I was bored during math class and tried to formalize my professor's claims

xy=xxxxrepeated y timesx^y = \underbrace{x \cdot x \cdots x \cdot x}_{\text{repeated } y \text{ times}}

this can be expressed more formally with a recursive definition

xxy=xy+1x \cdot x^y = x^{y+1}

x1=xx^1 = x


x1=xx^1 = x is very intuitive, however, from these simple definitions, one can show that x0=1x^0 = 1:

xx0=x1=xx \cdot x^0 = x^1 = x

the only multiplicative identity there is (in R\mathbb{R}) is 11, so x0=1x^0 = 1


you can show that xaxb=xa+bx^a \cdot x^b = x^{a+b} easily by using the informal definition:

xaxb=xxxxrepeated a timesxxxxrepeated b timesrepeated a+b times=xa+bx^a \cdot x^b = \overbrace{\underbrace{x \cdot x \cdots x \cdot x}_{\text{repeated } a \text{ times}} \cdot \underbrace{x \cdot x \cdots x \cdot x}_{\text{repeated } b \text{ times}}}^{\text{repeated } a + b \text{ times}} = x^{a+b}

however, proving it formally is harder

xy=xxy1x^y = x \cdot x^{y-1}

xaxb=xa1xxb=xa1xb+1x^a \cdot x^b = x^{a-1} \cdot x \cdot x^b = x^{a-1} \cdot x^{b+1}

inductively,

xaxb=xanxb+nx^a \cdot x^b = x^{a-n} \cdot x^{b+n}

when n=an=a,

xaxb=xaaxb+a=x0xb+a=1xb+a=xa+bx^a \cdot x^b = x^{a-a} \cdot x^{b+a} = x^0 \cdot x^{b+a} = 1 \cdot x^{b+a} = x^{a+b}


the final property to be shown is that (xa)b=xab(x^a)^b = x^{a \cdot b}, I actually find this one easier to prove formally than to try to understand it intuitively

(xa)b=xa(xa)b1(x^a)^b = x^a \cdot (x^a)^{b-1}

if we multiply both sides by xanx^{an},

xan(xa)b=xanxa(xa)b1=xan+a(xa)b1=xa(n+1)(xa)b1x^{an} \cdot (x^a)^b = x^{an} \cdot x^a \cdot (x^a)^{b-1} = x^{an+a} \cdot (x^a)^{b-1} = x^{a(n+1)} \cdot (x^a)^{b-1}

inductively,

xan(xa)b=xa(n+m)(xa)bmx^{an} \cdot (x^a)^b = x^{a(n+m)} \cdot (x^a)^{b-m}

when n=0n=0,

xa0(xa)b=x0(xa)b=(xa)b=xa(0+m)(xa)bm=xam(xa)bmx^{a0} \cdot (x^a)^b = x^0 \cdot (x^a)^b = (x^a)^b = x^{a(0+m)} \cdot (x^a)^{b-m} = x^{am} \cdot (x^a)^{b-m}

when m=bm=b,

(xa)b=xam(xa)bb=xab(xa)0=xab(x^a)^b = x^{am} \cdot (x^a)^{b-b} = x^{ab} \cdot (x^a)^0 = x^{ab}